Actively switchable terahertz Spiral-Shaped metamaterial with programmable performance. (February 2023) - Feng, Qiuxiao; Zheng, Daoye; Liu, Yuwei; Chen, Peiyu; Lin, Yu-Sheng
Highlights: Two actively switchable THz spiral-shaped metamaterials (SSMs) are presented. SSMs are composed of four spiral meta -atoms with different orientations. SSMs show the fifth-resonance to provide five switching windows for binary encoding characteristic. SSMs possess the binary encoding and logic operation such as NAND and OR gates. SSM designs can be promising optoelectronic switching and multi-bit programmable devices. Abstract: Two designs of actively switchable terahertz (THz) spiral-shaped metamaterial (SSM) are presented in this study. They are composed of four spiral meta -atoms with different orientations. The electromagnetic responses of SSM devices show the fifth-resonance to provide five switching windows for binary encoding due to their transmission intensities with polarization-dependent characteristic. In addition, by actively changing the configuration of elevated spiral meta -atoms, a dual-resonance switching function can be realized. It proves the binary encoding and logic operation such as NAND and OR gates. These characteristics indicate that the proposed SSM designs can be promising optoelectronic switching and multi-bit programmable devices in the THz spectrum.